Urgensi Seks Education pada Peserta Didik di MI sebagai Upaya Penanggulangan Kekerasan Seksual pada Anak di Era Society 5.0 - Putri Dewi Fatimah; Elya Umi Hanik (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
There is a lot of sexual violence that occurs in Indonesia, especially against children/students in MI/SD. Students who should be learning, playing, happy but because of the trauma experienced after the sexual violence affects their daily lives. Therefore, the importance of sex education at this time in order to overcome the occurrence of sexual violence experienced by students. In addition, sex education is used to raise awareness and inform parents about the importance of sex education in children from an early age. The method used in writing this article is a literature search while the analytical method used is descriptive qualitative analysis. Then, from the research that has been done, it can be concluded that the results of this research are the urgency of sex education in the era of society 5.0. It can be said that it has succeeded in becoming a countermeasure when all parties, be it parents, teachers, the community or other parties, work together in carrying out this effort, not only Therefore, with the sophistication that exists in the era of society 5.0, it is hoped that sexual violence can be overcome so that no more sexual violence occurs to students.Keywords: Sex education, students, sexual violence